Sustainable active packaging for the EU green transition: HEC/vitamin C antioxidant films enhancing food safety and reducing waste - Arman Kandirmaz, Emine; Ozcan, Arif (Journal of Graphic Engineering and Design, 2025)
The growing demand for sustainable food packaging is driven not only by consumer awareness of food safety but also by international strategies such as national development plans and European Union regulations, which emphasize the replacement of conventional plastics with bio-based and functional alternatives. In this context, active antioxidant packaging plays a critical role in extending food shelf life, reducing waste, and ensuring safer products. Hydroxyethyl cellulose (HEC) was selected as the matrix material due to its good film-forming properties, biodegradability, biocompatibility, odorlessness, and non-toxicity or low toxicity, while vitamin C (ascorbic acid), a natural antioxidant, was incorporated as the active agent. HEC solution was prepared by dissolving HEC powder in distilled water, and vitamin C was incorporated. The resulting mixtures were homogenized and cast onto glass plates, followed by drying to produce uniform films. The obtained films were systematically characterized in terms of contact angle (wettability), and antioxidant capacity. In addition, their surface performance was evaluated through IGT F1 flexographic test printing trials to assess practical applicability. The results demonstrated that the incorporation of vitamin C enhanced the antioxidant functionality of HEC films, while altering their barrier and surface properties depending on the concentration used. These findings suggest that HEC-based films containing vitamin C have significant potential as active packaging materials that meet both sustainability goals and food safety requirements. Article history: Received (October 3, 2025); Revised (October 27, 2025); Accepted (November 10, 2025)